2011
DOI: 10.1007/s00330-011-2240-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for non-spinal osteoid osteomas in 557 patients

Abstract: Electrode parameters, duration of ablation, morphology and size of osteoid osteomas are important for RFA. The above modifications are recommended for improved outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 29 publications
7
63
0
2
Order By: Relevance
“…The more recent studies report comparable primary technique effectiveness of 85%-100% (32)(33)(34)(35). One factor leading to the high success and low relapse rate in our study might be the longer ablation time compared with some previous studies (10), which is corroborated by the data of other studies with similar findings (24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The more recent studies report comparable primary technique effectiveness of 85%-100% (32)(33)(34)(35). One factor leading to the high success and low relapse rate in our study might be the longer ablation time compared with some previous studies (10), which is corroborated by the data of other studies with similar findings (24).…”
Section: Discussionsupporting
confidence: 89%
“…General information about the RFA technique is provided in previous studies (7)(8)(9)(20)(21)(22)(23)(24). The specific technical considerations used in our study are as follows: The procedure was performed under general (70 patients) or spinal (two patients) anesthesia.…”
Section: Rfa Techniquementioning
confidence: 99%
“…Although OO is benign and spontaneous remission occasionally occurs, an intervention for definitive relief of pain is sometimes required [2]. Among others techniques [3], radiofrequency ablation (RFA) is a minimally invasive technique which allows thermal destruction of the OO [4][5][6]. The most common location of OO is in the long bones [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among others techniques [3], radiofrequency ablation (RFA) is a minimally invasive technique which allows thermal destruction of the OO [4][5][6]. The most common location of OO is in the long bones [5]. Most OOs are cortical and macroscopically consist of a nidus of active bone surrounded by a reactive zone.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of RF ablation of OOs localized in the extremities and pelvis has been proven by many studies. [16][17][18][19] Percutaneous RF ablation for the treatment of spinal OOs is not widely used, probably owing to the potential danger to the adjacent neural and vascular elements. In recent years, however, some clinical studies reported good results in the management of spinal OOs using CT-guided RF ablation.…”
Section: Advances In Knowledgementioning
confidence: 99%